2011
DOI: 10.1002/elps.201000503
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of electrokinetic translocation of a cylindrical particle through a nanopore using a Poisson–Boltzmann approach

Abstract: Nanopore-based sensing of single molecules is based on a detectable change in the ionic current arising from the electrokinetic translocation of individual nanoparticles through a nanopore. In this study, we propose a continuum-based model to investigate the dynamic electrokinetic translocation of a cylindrical nanoparticle through a nanopore and the corresponding ionic current response. It is the first time to simultaneously solve the Poisson-Boltzmann equation for the ionic concentrations and the electric fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 54 publications
1
21
0
1
Order By: Relevance
“…55, 7577, 8587 Ai and Qian recently modeled the dynamics of nanorods (1 nm × 10 nm) approaching a nanopore under similar conditions to those reported here and demonstrated that rods will completely align with their length axis parallel to the electric field prior to entering the nanopore. 88 Furthermore, the distribution of translocation times in cluster (ii) was narrower than the distribution in cluster (i) (Figure 2B). This result suggests reduced diffusive spreading due to accelerated motion through the pore as a result of reduced viscous drag on aggregates in cluster (ii) compared to those in cluster (i) (see Supporting Information S6 for distributions of t d values in clusters i and ii).…”
Section: Resultsmentioning
confidence: 88%
“…55, 7577, 8587 Ai and Qian recently modeled the dynamics of nanorods (1 nm × 10 nm) approaching a nanopore under similar conditions to those reported here and demonstrated that rods will completely align with their length axis parallel to the electric field prior to entering the nanopore. 88 Furthermore, the distribution of translocation times in cluster (ii) was narrower than the distribution in cluster (i) (Figure 2B). This result suggests reduced diffusive spreading due to accelerated motion through the pore as a result of reduced viscous drag on aggregates in cluster (ii) compared to those in cluster (i) (see Supporting Information S6 for distributions of t d values in clusters i and ii).…”
Section: Resultsmentioning
confidence: 88%
“…30−34 The translocation of cylindrical particles was reported with a biphasic pulse at salt concentration 0.01 M and the electrokinetic motion was shown by simulation. 35,36 The cation and anion distributions were also shown in ref 35 where they are not equal to the bulk concentration. Goyal (2013) investigated gold nanoparticle translocation using silicon nitride nanopores and observed ionic current enhancement upon particle translocation in 20 mM KCl solution.…”
Section: Introductionmentioning
confidence: 80%
“…Cylindrical particle flow is a frequent industrial process application, for example indirect combustion of biomass straws, moulding and drying of cylindrical pills, and moulding and machining of composite materials of fibres. Many studies have shown that the gas‐solid flow characteristics involving cylindrical particles are distinctly different from those involving spherical particles . However, it is extremely difficult (if not impossible) to experimentally acquire valuable cylindrical particle flow parameters because of present limited equipment and measuring technique levels.…”
Section: Introductionmentioning
confidence: 99%